Intention to Use Islamic Fintech Which is Influenced by Sharia Compliance Variabels, Perceived Usefulness, Islamic Religiosity and Perceived Ease of Use - Permana, Daffa Abdi; Syihabudin; Najmudin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study aims to determine whether sharia compliance, perceived usefulness, Islamic religiosity and perceived convenience partially or simultaneously have a positive and significant effect on the intention to use sharia fintech. This type of research uses quantitative research with descriptive and associative approaches. The sample in the study amounted to 82 respondents. The data analysis technique used is instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination (R2) analysis with SPSS version 26.0 program. The results of data analysis show that the results of the partial test (t test), sharia compliance, perceived usefulness and perceived convenience partially have a positive and significant effect on the intention to use sharia fintech, while Islamic religiosity has no significant effect. The simultaneous test results (F test) show that F count (44,526) > F table (2.72) with a significance value of 0.000 <0.05. It can be concluded that sharia complianc, perceived usefulness, Islamic religiosity and perceived convenience simultaneously have a positive and significant effect on the intention to use Islamic fintech.